Glucocorticoids Target Ependymal Glia and Inhibit Repair of the Injured Spinal Cord - Nelson, Craig M.; Lennon, Vanda A.; Lee, Han; Krug, Randall G.; Kamalova, Aichurok; Madigan, Nicolas N.; Clark, Karl J.; Windebank, Anthony J.; Henley, John R. (Frontiers in Cell and Developmental Biology, 2019)
Abstract Following injury, the mammalian spinal cord forms a glial scar and fails to regenerate. In contrast, vertebrate fish spinal cord tissue regenerates completely to restore function. Cord transection in zebrafish (Danio rerio) initially causes paralysis and neural cell death. Subsequently, ependymal glia proliferate, bipolar glia extend across the lesion, and new neurons are born; axons from spared and nascent neurons extend along trans-lesional glial bridges to restore functional connectivity. Here we report that glucocorticoids, used in the clinical management of spinal cord injury, directly inhibit neural repair by targeting ependymal glia independently of hematogenous cells and microglia. After transecting injury, the glucocorticoid receptor in ependymal glia is regulated differentially in zebrafish (becoming inactive) vs. the rat (becoming active). Glucocorticoid blockade of neural regeneration via a direct effect on ependymal glia has important therapeutic implications for the putative benefit of corticosteroids in early management of spinal cord injury.